Habitus, Heterotopia and Endocolonialism in Early Spanish Literary Fascism - Nil Santiáñez (Studies in 20th & 21st Century Literature, 2009)
This article explores strategies of symbolic production of national space (e.g. technologies of tropological striation) in early fascist works of Tomás Borrás, Luys Santa Marina, and Rafael Sánchez Mazas written à propos the Rif War (1919-27). Considered as perlocutionary speech-acts, these texts conceive Morocco as a heterotopia and embody a fascist habitus produced by a heterogeneous group of writers, intellectuals, politicians and military personnel—in particular the notorious Foreign Legion—posted in Morocco; they all shared the defense of an authoritarian concept of nation as a model for the political organization of Spain as well as an endocolonialist gaze and stance towards their own country. By means of its tropological conquest of Moroccan territory, Fascist writing devoted to the Rif War duplicated the empirical spatial production carried out in situ by the army and the civilian administration of the Spanish protectorate of Morocco. Making it intelligible as well as modifying it, such writing brought to the Peninsula an endocolonial project and an incipient fascist habitus. Its development in the 1930s (the theory of fascism, Falange Española, the Falangists’ direct action in the streets of Spain, the tactics and strategy followed by the High Command of Franco’s army during the civil war) would culminate after 1939 in the empiric production of a new administrative, political and economic organization of Spain’s national territory.
Keywords: fascist; national space; Borrás; Santa Marina; Sánchez Mazas; Morocco; heterotopia; endocolonialism; Franco; national territory